Peningkatan Profesionalisme Pendidik melalui Pelatihan Penulisan Artikel Ilmiah di Kota Mataram - Herianto, Edy; Ismail, M.; Sumardi, Lalu; Edi, Maria Grace Putri; Jumrawati, Jumrawati; Hidayah, Nurul; Yarti, Suci; Listianingsih, Wulan; MZ, Astiana Soparia; Istiningsih, Siti (Jurnal Gema Ngabdi, 2025)
This community service program aimed to enhance teacher professionalism through scientific article writing training in Mataram City. The program was motivated by the low academic writing competence among teachers, with only about 30% having prior publication experience. A total of 35 participants, consisting of 25 junior high school teachers and 10 pre-service teachers, were involved in activities that included socialization, intensive workshops, mentoring, and the use of supporting technologies such as Mendeley, Turnitin, and Google Classroom. Evaluation through pre-test and post-test demonstrated an improvement in participants’ scores from 67% to 78%, representing an 11% increase, with the highest achievement in academic ethics (85%). Furthermore, participants successfully developed article drafts, one of which was prepared for submission to a SINTA 4–accredited journal, and established a scientific writing community along with the production of a textbook Writing Educational Articles: From Ideas to Publication as additional outputs. These results indicate that practice-based training, personal mentoring, and the integration of technology are effective in improving academic literacy and teacher professionalism. The novelty of this program lies in combining academic literacy training with the creation of sustainable outputs (textbook and community), making it a replicable model for other regions with similar challenges.